Recasting Antiquarianism as Confucian Orthodoxy: Wang Zuo’s Expanded Essential Criteria of Antiquities and the Moral Reinscription of Material Culture in the Ming Dynasty - Ziming Chen; Hanwei Wang (Religions)
This article examines Xinzeng Gegu yaolun 新增格古要論 (Expanded Essential Criteria of Antiquities), a connoisseurship manual compiled in 1460 by the mid-Ming official Wang Zuo 王佐. Drawing upon Cao Zhao’s 曹昭 early Ming Gegu yaolun 格古要論 (Essential Criteria of Antiquities), Wang reconfigured a manual focused on authentication and appreciation into a text structured by Confucian values and political ethics. He added ritual-oriented entries in chapters four and ten through thirteen, such as “An Examination of Song Dynasty Attire and Rank Titles” 宋制服裝入銜考 and “An Inquiry into Gold and Silver Insignia” 佩金銀牌考, reinforcing Confucian ideology through commentary on ritual institutions and the inclusion of imperial edicts and commemorative inscriptions. He also reorganized the placement of guqin 古琴, calligraphy and painting, while redefining evaluative standards to integrate material objects into moral instruction and bureaucratic discipline. In doing so, Wang reinforced a shared community of scholar–officials, using ritual hierarchy, loyalist writings, and gift exchange to respond to the uncertainty of a fractured political order. This article argues that through a non-canonical text like Xinzeng Gegu yaolun, mid-Ming scholar–officials extended Confucian discourse into antiquities, transforming antiquarian writing into a visible enactment of ethical values and collective identity.